2013
DOI: 10.1038/ni.2549
|View full text |Cite
|
Sign up to set email alerts
|

Fishing for mammalian paradigms in the teleost immune system

Abstract: Recent years have witnessed a renaissance in the study of fish immune systems. Such studies have greatly expanded the knowledge of the evolution and diversification of vertebrate immune systems. Several findings in those studies have overturned old paradigms about the immune system and led to the discovery of novel aspects of mammalian immunity. Here I focus on how findings pertaining to immunity in teleost (bony) fish have led to major new insights about mammalian B cell function in innate and adaptive immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(148 citation statements)
references
References 72 publications
6
141
1
Order By: Relevance
“…Further studies on the fish SALT and the IgT system will contribute to revealing some of these principles common to fish and mammals. In that regard, recent comparative studies on the fish immune system have been instrumental in unraveling previously unrecognized aspects of mammalian immunity (38). Additionally, from a more practical perspective, it is well known that the fish skin is a major portal of pathogens for which vaccines are still unavailable, including that used in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Further studies on the fish SALT and the IgT system will contribute to revealing some of these principles common to fish and mammals. In that regard, recent comparative studies on the fish immune system have been instrumental in unraveling previously unrecognized aspects of mammalian immunity (38). Additionally, from a more practical perspective, it is well known that the fish skin is a major portal of pathogens for which vaccines are still unavailable, including that used in this study.…”
Section: Discussionmentioning
confidence: 97%
“…To understand their pathogenetic mechanisms and thereby provide protective strategies again them, some significant experimental methods and high-throughput technologies such as transcriptomics and proteomics have been recently used to gain better knowledge of these viruses and their hosts. Such studies have greatly expanded our knowledge about the innate and acquired immune systems of aquatic animals [151][152][153][154][155]. In China especially, comparative immunological studies of aquaculture animals have flourished over the last 10 years, financial support for research in this area has increased, and progress in this field has been reported in several reviews [156][157][158][159][160][161][162].…”
Section: Virus-host Interactions In Aquatic Animalsmentioning
confidence: 99%
“…The teleost fish models have greatly contributed to innate immune system study (Rauta et al 2012, Sunyer 2013. The fish embryonic development usually occurs outside of the maternal body in an aqueous environment, in which the embryos are potentially susceptible to microbial pathogens.…”
Section: Introductionmentioning
confidence: 99%